Flood inundation modeling in ungauged basins using Unmanned Aerial Vehicles imagery - Yavari, Adel; Homayouni, Saeid; Oubennaceur, Khalid; Chokmani, Karem (Earth Observation and Geomatics Engineering, 2020)
This paper presents a new framework for floodplain inundation modeling in an ungauged basin using unmanned aerial vehicles (UAVs) imagery. This method is based on the integrated analysis of high-resolution ortho-images and elevation data produced by the structure from motion (SfM) technology. To this end, the Flood-Level Marks (FLMs) were created from high-resolution UAV ortho-images and compared to the flood inundated areas simulated using the HEC-RAS hydraulic model. The flood quantiles for 25, 50, 100, and 200 return periods were then estimated by synthetic hydrographs using the Natural Resources Conservation Service (NRCS). The proposed method was applied to UAV image data collected from the Khosban village, in Taleghan County, Iran, in the ungauged sub-basin of the Khosban River. The study area is located along one kilometre of the river in the middle of the village. The results showed that the flood inundation areas modeled by the HEC-RAS were 33%, 19%, and 8% less than those estimated from the UAV’s FLMs for 25, 50, and 100 years return periods, respectively. For return periods of 200 years, this difference was overestimated by more than 6%, compared to the UAV’s FLM. The maximum flood depth in our four proposed scenarios of hydraulic models varied between 2.33 to 2.83 meters. These analyses showed that this method, based on the UAV imagery, is well suited to improve the hydraulic modeling for seasonal inundation in ungauged rivers, thus providing reliable support to flood mitigation strategies
Publisher: University of Tehran Press

Imaging Floods and Glacier Geohazards with Remote Sensing - Cigna, Francesca; Xie, Hongjie (Remote Sensing, 2020)
Geohazards associated with the dynamics of the liquid and solid water of the Earth’s hydrosphere, such as floods and glacial processes, may pose significant risks to populations, activities and properties [...]
Number: 23 Publisher: Multidisciplinary Digital Publishing Institute

Short-term water quality variable prediction using a hybrid CNN–LSTM deep learning model - Barzegar, Rahim; Aalami, Mohammad Taghi; Adamowski, Jan (Stochastic Environmental Research and Risk Assessment, 2020)

Développement et analyse d'une méthode de cartographie de la submersion côtière dans l'estuaire et le golfe du Saint-Laurent, Qc - Didier, David (Université du Québec à Rimouski, 2020)
RÉSUMÉ: Les événements de submersion sont en augmentation sur les côtes du fleuve Saint-Laurent en raison des tempêtes, de la hausse du niveau marin et de la diminution de la glace de mer. À ce jour, le Québec ne possède pas de zonage de la submersion. Dans le cadre de cette thèse, une approche de cartographie de la submersion est développée en intégrant les vagues, les niveaux d'eau et la morphologie des plages de l'estuaire et du golfe du Saint-Laurent (EGSL). Deux types d'approches cartographiques ont été comparés : la simulation empirique qui projette un niveau total statique sur le territoire (niveau d'eau observé + effet des vagues sur la côte, le jet de rive ou runup), et le modèle numérique XBeach en mode surfbeat. Ces deux approches nécessitent une surface topo-bathymétrique précise et actualisée de la plage. Grâce au développement d'un réseau de suivi des plages par vidéo, nous évaluons dans un premier temps l'efficacité d'une méthode de topographie intertidale par vidéo par rapport à des levés LiDAR terrestres, et améliorons sa performance en intégrant les niveaux d'eau près de la plage au module d'élévation des lignes d'eau. Ce projet a permis la création de surfaces topographiques à précision centimétrique comparable au LiDAR et d'y extraire des paramètres morphologiques, comme la pente de la plage, nécessaire aux modèles empiriques de niveaux d'eau. La capacité des deux approches de cartographie à simuler la submersion du 6 décembre 2010 au Bas-Saint-Laurent a ensuite été analysée en comparant les surfaces inondées. La correspondance spatiale entre les simulations et les observations de submersion a été évaluée. Il en ressort que malgré la complexité du modèle XBeach et une légère surprédiction du modèle empirique (36%), les surfaces submergées obtenues par les deux approches sont similaires et correctement prédites à hauteur de 66-78%. Dans le cadre d'une troisième étude, XBeach a également été utilisé dans la baie des Chaleurs pour évaluer l'impact d'un événement extrême pour l'horizon 2100 sur l'aléa de submersion. Les simulations montrent que les débordements côtiers ont été engendrés par des vagues de relativement faible amplitude à la côte (Hs < 1 m) et que malgré des profondeurs d'eau avoisinant 1,2 m, des vitesses de courants élevées se sont produites dans les espaces urbanisés (U > 2 m/s). L'analyse de la cartographie de la submersion à Maria suggère qu'en 2100, l'impact de la hausse du niveau marin sur les communautés riveraines du Saint-Laurent pourrait provoquer des submersions plus vastes avec des profondeurs d'eau et vitesses de courants plus élevées, ce qui pourraient intensifier l'aléa auquel fait face la population. Même si les simulations numériques permettent de comprendre comment les phénomènes physiques engendrent la submersion, l'intérêt de la méthode statique réside dans sa rapidité d'application, mais son efficacité est fonction de la validité et l'applicabilité des modèles empiriques de runup utilisés. Ainsi, le dernier volet de la thèse porte sur le paramétrage d'un modèle empirique de runup adapté à l'EGSL. L'observation du runup (et de ses composantes moyenne et haute fréquence, le setup et le swash) par vidéo réalisée sur 5 plages couvre un large spectre de paramètres environnementaux et de types de côte sur une période de 3 ans. Des analyses de corrélation entre les niveaux d'eau à la côte et les caractéristiques de vagues au large et la pente de plage ont été réalisées. Les résultats montrent que l'influence des paramètres hydrodynamiques sur le runup, setup, et swash est paramétrée de façon similaire. Le rôle de la morphologie de la plage sur le setup est par ailleurs paramétré par une fonction inverse de la pente, alors que le swash est fonction de la racine carrée de la pente. Avec une erreur moyenne de 23 cm et un biais de 2 cm, l'équation de runup proposée offre un fort potentiel d'estimation des niveaux d'eau totaux sur les environnements côtiers diversifiés à fetch limité. Les résultats de la thèse montrent qu'il apparaît pertinent d'utiliser une approche statique p ur identifier les zones les plus vulnérables à la submersion, en autant que l'équation utilisée soit validée sur le type d'environnement en question. En combinant cette approche à des modélisations numériques en zones à forte concentration d'enjeux, il sera possible d'instaurer un premier zonage de la submersion au Québec. – Mot(s) clé(s) en français : Cartographie de la submersion, Runup, Topographie par vidéo, Vagues infragravitaires, XBeach. – ABSTRACT: Coastal flood events are increasing on the shores of the St. Lawrence River due to storms, rising sea levels and decreasing sea ice. To date, the province of Québec does not have a coastal flood mapping guideline. In this thesis, a coastal flood mapping approach is developed by integrating waves, water levels and beach morphology of the Estuary and Gulf of St. Lawrence (EGSL). Two types of cartographic approaches were compared: the empirical simulation that projects a static total level overland (observed water level + wave effect on the coast, known as wave runup), and the numerical model XBeach in surfbeat mode. These two approaches require a precise and updated topo-bathymetric surface of the beach. Through the development of a shore-based video monitoring network, we first evaluate the effectiveness of a video intertidal topography method against terrestrial LiDAR surveys, and improve its performance by integrating water levels near the beach as a proxy to beach contour elevetion. This project enabled the creation of centimeter-scale topographic surfaces comparable to LiDAR and the extraction of morphological parameters, such as the beach slope, necessary for empirical runup models. The ability of both mapping approaches to simulate the flood of December 6, 2010 in Bas-Saint-Laurent was analyzed by comparing flooded areas. Spatial correspondence between simulations and the observed flood extent was evaluated. Despite the complexity of XBeach and a slight over-prediction of the empirical model (36%), the flooded areas obtained by the two approaches are similar and correctly predicted by 66-78%. In a third study, XBeach was also used in the Chaleur Bay to assess the impact of an extreme event for the 2100 horizon on coastal flood hazards. The simulations show that the overland flow was generated by waves of relatively low amplitude at the coast (Hs <1 m) and that despite water depths close to 1.2 m, high current velocities occurred in the urbanized areas (U> 2 m/s). The analysis of the flood maps in Maria suggests that by 2100, the impact of sea level rise on coastal communities in the St. Lawrence could lead to larger flooded areas, with deeper water depths and higher flow velocity, intensifying the risk to the population. Although numerical simulations offer an understanding of the physical phenomena that cause coastal flooding, the interest of the static method lies in its convenience, but its effectiveness depends on the validity of the empirical runup models employed. Thus, the last part of the thesis deals with the parameterization of an empirical runup model in the EGSL. Video-based wave runup observations (and of its mean and high frequency components, setup and swash, respectively) on 5 beaches was carried out on a broad spectrum of environmental parameters and coast type over a period of 3 years. Correlation analyzes between coastal water levels (runup, setup, and swash) and offshore wave characteristics and beach slope were performed. The results show that the influence of the hydrodynamic parameters on wave runup, setup, and swash is similarly parameterized. The role of the morphology of the range on the setup is however parameterized by an inverse function of the slope, while the swash is a function of the square root of the slope. With an average error of 23 cm and a 2 cm bias, the original runup equation offers a high potential for estimating total water levels over diverse fetch-limited coastal environments. This thesis shows that it seems appropriate to use a static approach to identify the areas most vulnerable to coastal flooding, as long as the equation used is validated on the specific coastal environment. By combining this approach with numerical modeling in coastal hotspots with multiple issues at stake, it will be possible to introduce a first coasta flood zoning in the province of Québec. – Mot(s) clé(s) en anglais : Coastal flooding, Runup, Video-derived topography, Infragravity waves, XBeach.

Flood Hazard Risk Mapping Using a Pseudo Supervised Random Forest - Esfandiari, Morteza; Abdi, Ghasem; Jabari, Shabnam; McGrath, Heather; Coleman, David (Remote Sensing, 2020)
Devastating floods occur regularly around the world. Recently, machine learning models have been used for flood susceptibility mapping. However, even when these algorithms are provided with adequate ground truth training samples, they can fail to predict flood extends reliably. On the other hand, the height above nearest drainage (HAND) model can produce flood prediction maps with limited accuracy. The objective of this research is to produce an accurate and dynamic flood modeling technique to produce flood maps as a function of water level by combining the HAND model and machine learning. In this paper, the HAND model was utilized to generate a preliminary flood map; then, the predictions of the HAND model were used to produce pseudo training samples for a R.F. model. To improve the R.F. training stage, five of the most effective flood mapping conditioning factors are used, namely, Altitude, Slope, Aspect, Distance from River and Land use/cover map. In this approach, the R.F. model is trained to dynamically estimate the flood extent with the pseudo training points acquired from the HAND model. However, due to the limited accuracy of the HAND model, a random sample consensus (RANSAC) method was used to detect outliers. The accuracy of the proposed model for flood extent prediction, was tested on different flood events in the city of Fredericton, NB, Canada in 2014, 2016, 2018, 2019. Furthermore, to ensure that the proposed model can produce accurate flood maps in other areas as well, it was also tested on the 2019 flood in Gatineau, QC, Canada. Accuracy assessment metrics, such as overall accuracy, Cohen’s kappa coefficient, Matthews correlation coefficient, true positive rate (TPR), true negative rate (TNR), false positive rate (FPR) and false negative rate (FNR), were used to compare the predicted flood extent of the study areas, to the extent estimated by the HAND model and the extent imaged by Sentinel-2 and Landsat satellites. The results confirm that the proposed model can improve the flood extent prediction of the HAND model without using any ground truth training data.

Large Scale Flood Risk Mapping in Data Scarce Environments: An Application for Romania - Albano, Raffaele; Samela, Caterina; Crăciun, Iulia; Manfreda, Salvatore; Adamowski, Jan; Sole, Aurelia; Sivertun, Åke; Ozunu, Alexandru (Water, 2020)
Large-scale flood risk assessment is essential in supporting national and global policies, emergency operations and land-use management. The present study proposes a cost-efficient method for the large-scale mapping of direct economic flood damage in data-scarce environments. The proposed framework consists of three main stages: (i) deriving a water depth map through a geomorphic method based on a supervised linear binary classification; (ii) generating an exposure land-use map developed from multi-spectral Landsat 8 satellite images using a machine-learning classification algorithm; and (iii) performing a flood damage assessment using a GIS tool, based on the vulnerability (depth–damage) curves method. The proposed integrated method was applied over the entire country of Romania (including minor order basins) for a 100-year return time at 30-m resolution. The results showed how the description of flood risk may especially benefit from the ability of the proposed cost-efficient model to carry out large-scale analyses in data-scarce environments. This approach may help in performing and updating risk assessments and management, taking into account the temporal and spatial changes in hazard, exposure, and vulnerability.